omparison of CSMC (Cedar Sinai Medical Center) QGS/QPS (Quantitative Gated SPECT/Quantitative Perfusion SPECT) and INVIA-4 Dimension Myocardial SPECT Softwares for Quantitative Analysis of Left Ventricular Perfusion and Function in Gated Myocardial SPECT Scintigraphy - Sikandar, Zeeshan; Hussain, Fida; Adil, Muhammad; Atif, Muhammad; Malik, Asad; Shameela, Hafiza (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare left ventricular parameters using Quantitative Perfusion SPECT / Quantitative Gated SPECT (QPS / QGS) and 4 Dimension-Myocardial SPECT (4-DM) softwares.Study Designs: Analytical Cross Sectional studyPlace and Duration of Study: Nuclear Medical Centre, Armed Forces Institute of Pathology Rawalpindi, Pakistan from Jun 2022  to Jun 2023.Methodology: One hundred and thirty seven patients with suspicion of coronary artery disease underwent myocardial perfusion scan during study duration. The patients underwent stress and rest gated SPECT imaging using a single day protocol. All the images were processed using QGS / QPS and 4-DM softwares separately and left ventricular parameters including Summed Stress Score (SSS), Summed Rest Score (SRS), Summed Difference Score (SDS), End Diastolic Volume (EDV), End Systolic Volume (ESV) and Ejection Fraction (EF) were calculated. Mean values and relationship between both softwares were calculated.Results: Out of 137 patients, 80(58.4%) were men and 57(41.6%) were women with mean age of 56.29±15.17 years. The mean SSS, SRS, SDS, EDV, ESV and EF by QGS was 9.83±8.08, 6.24±6.01, 2.54±2.18, 93.94±42.73 ml, 48.04±38.16 ml and 55.94±18.06 %. While by 4-DM was 9.07±7.41, 6.72±6.39, 2.84±2.51, 97.64±43.46 ml, 45.02±40.29 ml, 61.59±18.36 % respectively. All the left ventricular parameters including SSS, SRS, SDS, EDV, ESV and EF as measured by both softwares showed substantial variation with a p-value of